Area and production estimates for vineyards - Iulia Bianca Bogos; Ionut Laurentiu Petre; Maria Cristina Sterie (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Viticulture is an important activity in Romania, with a tradition since ancient times, it is ideal to cultivate especially for its geographical position and pedo-climatic conditions. In Romania, the area under vines is decreasing between 2015 and 2021, while total grape production is increasing considerably during this period. At EU level, Romania ranks 5th in terms of vineyard area and 6th in terms of total grape production, behind countries such as Italy, Germany, France, Portugal and Spain. Using the Forecast method, it is estimated that in 2030 the area under vines will reach 149 thousand hectares, the optimistic scenario shows that the area will reach 156 thousand hectares and the pessimistic scenario shows that the area will reach 99 thousand hectares. In the case of total grape production, it is estimated that in 2030, Romania will produce 99 thousand tonnes, according to the pessimistic scenario it will reach 1.42 million tonnes, and according to the pessimistic scenario it will reach 400 thousand tonnes.
Keywords: Q10; L66; C13; 330; estimates; viticulture; Romania